Efficient Continuous Light‐Driven Electrochemical Water Splitting Enabled by Monolithic Perovskite‐Silicon Tandem Photovoltaics. Issue 2 (10th November 2022) - Datta, Kunal; Branco, Bruno; Zhao, Yifeng; Zardetto, Valerio; Phung, Nga; Bracesco, Andrea; Mazzarella, Luana; Wienk, Martijn M.; Creatore, Mariadriana; Isabella, Olindo; Janssen, René A. J.
Abstract: Solar‐assisted water electrolysis is a promising technology for storing the energy of incident solar irradiation into hydrogen as a fuel. Here, an integrated continuous flow electrochemical reactor coupled to a monolithic perovskite‐silicon tandem solar cell is demonstrated that provides light‐driven electrochemical solar‐to‐hydrogen conversion with an energy conversion efficiency exceeding 21% at 1‐Sun equivalent light intensity and stable operation during three simulated day‐night cycles. Abstract : Solar‐assisted water splitting using a flow electrochemical cell and a monolithic perovskite‐silicon tandem solar cell is used to generate hydrogen at a solar‐to‐hydrogen efficiency of >21% at 1‐Sun equivalent light intensity.